Q. 14.1( 23 Votes )

Mark the correct

Answer :

Here, Question is


Now, A'=UA


(A' )'=(UA)'=U'A'


(A' )'=U'(UA)


(A' )'=ϕU+A


(A' )'=A

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove that A <spaRS Aggarwal - Mathematics

if U = {a, b, c} RS Aggarwal - Mathematics

For any two sets RD Sharma - Mathematics

For any two sets RD Sharma - Mathematics

For any two sets RD Sharma - Mathematics

If A, B, C are thRD Sharma - Mathematics

For any two sets RD Sharma - Mathematics

For any two sets RD Sharma - Mathematics

For any two sets RD Sharma - Mathematics

For any two sets RD Sharma - Mathematics